2020
DOI: 10.1097/wco.0000000000000786
|View full text |Cite
|
Sign up to set email alerts
|

RNA expression studies in stroke: what can they tell us about stroke mechanism?

Abstract: Purpose of review Diagnosis of stroke and understanding the mechanism of stroke is critical to implement optimal treatment. RNA expressed in peripheral blood cells is emerging as a precision biomarker to aid in stroke diagnosis and prediction of stroke cause. In this review, we summarize available data regarding the role of RNA to predict stroke, the rationale for these changes, and a discussion of novel mechanistic insight and clinical applications. Recent finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The early mortality rate of cerebral infarction is as high as 10% and 12%, and within a few years after acute events in patients with stroke, the mortality rate is still higher compared to the general population; it can also bring about 80% of survivors with permanent disability, often requiring special care and long-term rehabilitation [ 2 ]. Therefore, stroke has the characteristics of high incidence, high disability rate, and high mortality rate; it often causes huge human and economic losses [ 3 ]. Acute stroke, also known as ischemic stroke, is the most common type of stroke, accounting for 69.6% of stroke in China, accounting for 70.8%.…”
Section: Introductionmentioning
confidence: 99%
“…The early mortality rate of cerebral infarction is as high as 10% and 12%, and within a few years after acute events in patients with stroke, the mortality rate is still higher compared to the general population; it can also bring about 80% of survivors with permanent disability, often requiring special care and long-term rehabilitation [ 2 ]. Therefore, stroke has the characteristics of high incidence, high disability rate, and high mortality rate; it often causes huge human and economic losses [ 3 ]. Acute stroke, also known as ischemic stroke, is the most common type of stroke, accounting for 69.6% of stroke in China, accounting for 70.8%.…”
Section: Introductionmentioning
confidence: 99%
“…However, the narrow therapeutic window of its standard therapy and difficulty making a quick diagnosis in most under-resourced medical facilities (no brain imaging), necessitates the need to understand the molecular regulation of stroke and identification of its biomarkers. Such knowledge would enable the identification of quick biomarkers among differentially expressed proteins and mRNAs as well as provide novel insights into the mechanisms of stroke pathogenesis in patients [19,20]. Consequently, this study identified several stroke-induced changes in the expression of some circulating lncRNAs and their probable target of genes.…”
Section: Discussionmentioning
confidence: 98%
“…However, the narrow time window for treatment of its standard therapy and the difficulty in making a quick diagnosis in most low-resource medical facilities (no brain imaging) indicates a need to understand the molecular regulation of stroke and the identification of its biomarkers. Such knowledge would enable the identification of biomarkers among the DE proteins and mRNAs as well as to provide new opinions to the mechanisms of stroke pathogenesis in patients ( ENCODE Project Consortium, 2012 ; Falcione et al, 2020 ). Consequently, this study identified several stroke-induced changes in the expression of some circulating lncRNAs and their probable target genes.…”
Section: Discussionmentioning
confidence: 99%